2017
DOI: 10.1111/jomf.12401
|View full text |Cite
|
Sign up to set email alerts
|

Benefactors and Beneficiaries? Disability and Care to Others

Abstract: Individuals with disabilities often have limitations that require care from others to increase functioning and facilitate activities of daily living. Despite these care‐receiving needs, evidence suggests people with disabilities are also care givers. This study uses the 2008–2015 American Time Use Survey to examine the association between the presence of sensory, mental or cognitive, physical, or multiple limitations and the likelihood and intensity of time spent in primary child care, secondary child care, ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 86 publications
0
7
0
Order By: Relevance
“…The second equation was a negative binomial model that predicted the logged expected hours of physical activity, conditional on the probability that an individual will undertake any physical activity. To evaluate our hypotheses, we combined estimates from the logistic and negative binomial equations and plotted the predicted hours of physical activity (=[1 – π i ] × µ i ), where π i represents the fitted probability of no activity from the logit equation and µ i represents the predicted count from the negative binomial equation (Long and Freese 2014; Shandra and Penner 2017). We graphed predicted hours at the mean of all covariates in the model.…”
Section: Methodsmentioning
confidence: 99%
“…The second equation was a negative binomial model that predicted the logged expected hours of physical activity, conditional on the probability that an individual will undertake any physical activity. To evaluate our hypotheses, we combined estimates from the logistic and negative binomial equations and plotted the predicted hours of physical activity (=[1 – π i ] × µ i ), where π i represents the fitted probability of no activity from the logit equation and µ i represents the predicted count from the negative binomial equation (Long and Freese 2014; Shandra and Penner 2017). We graphed predicted hours at the mean of all covariates in the model.…”
Section: Methodsmentioning
confidence: 99%
“…In this regard, the study conducted by Nair and Wade [53] concerning the life goals of people with disabilities, highlighted that the most rated one was family. This is evident in a growing number of studies documenting how people with disabilities engage in multifaceted caregiving as a significant part of their daily lives [54]. More recently, time use studies indicate that people with work disabilities or functional limitations [55] and people receiving Social Security Disability Insurance (SSDI) [54] spend non-negligible amounts of time each day on caregiving, with care for others sometimes being greater relative to parenting due to the fatigue associated with physical disability [56,57], and with greater difficulties in accessing support than parents without disabilities [57].…”
Section: Plos Onementioning
confidence: 99%
“…Research on the groups of mothers explored in this study-those with physical and sensory disabilities-has shown variation in the particular challenges impairments present in carrying out the daily tasks of mothering. Mothers with physical disabilities often experience fatigue in managing the demands of caring and difficulties in negotiating inaccessible public spaces and private homes (Malacrida 2009;Shandra and Penner 2017). Deaf mothers frequently identify difficulties in obtaining interpreting services to participate fully in school activities and medical visits (Frederick 2015(Frederick , 2017aShandra and Penner 2017), while blind mothers have identified needing to expend energy in trial-and-error practices to develop effective ways of caring for their children (Frederick 2015(Frederick , 2017aShandra and Penner 2017).…”
Section: Mothers With Disabilitiesmentioning
confidence: 99%